Effects of sulfur additive on the transformation behaviors of γ‐Fe2O3 and coal liquefaction performances under mild conditions. Issue 4 (17th August 2018) - Zhao, Runze; Yang, Lan; Song, Xue; Zhang, Weishan; Wang, Baiyang; Huang, Sheng; Wu, Shiyong; Wu, Youqing
Abstract: In this paper, the effects of sulfur on liquefaction performances of coal and the transformation behaviors of γ‐Fe2 O3 at the S/Fe atomic ratio of 0–1.3 under mild conditions were investigated. Compared with traditional liquefaction processes, the oil yield and coal conversion were insensitive to the addition of sulfur under mild conditions (temperature of 430°C, reaction pressure of 8.5–13.8 MPa). The optimum S/Fe atomic ratios at the initial H2 pressures of 4.0 and 8.0 MPa were 0.6 and 1.0, which were lower than those of traditional liquefaction processes. As the S/Fe atomic ratio increased from 0 to 0.6 (at the initial H2 pressure of 4.0 MPa), the oil yield and coal conversion increased by 4.0% and 3.8%, and this could be attributed to the synergistic effects between the relatively sulfur‐rich structure of pyrrhotite (Fe0.8917 S) and the relatively high partial pressure of H2 S. In addition, over 85% of sulfur was retained in the solid products, and the effect of S/Fe atomic ratio on the sulfur distribution was tiny. However, increasing H2 pressure was conducive to the transfer of sulfur to the gaseous products.